Hypertensive emergencies in Asia: A brief review - Kotruchin, Praew; Tangpaisarn, Thanat; Mitsungnern, Thapanawong; Sukonthasarn, Apichard; Hoshide, Satoshi; Turana, Yuda; Siddique, Saulat; Buranakitjaroen, Peera; Huynh, Minh Van; Chia, Yook Chin *; Park, Sungha; Chen, Chen Huan; et al. (Wiley, 2022)
Hypertensive emergency is one of the most challenging conditions to treat in the emergency department (ED). From previous studies, about 1%-3% of hypertensive individuals experienced hypertensive emergencies. Its prevalence varied by country and region throughout Asia. Asian populations have more different biological and cultural backgrounds than Caucasians and even within Asian countries. However, there is a scarcity of research on clinical features, treatment, and outcomes in multinational Asian populations. The authors aimed to review the current evidence about epidemiology, clinical characteristics and outcomes, and practice guidelines in Asia. Five observational studies and nine clinical practice guidelines across Asia were reviewed. The prevalence of hypertensive emergencies ranged from .1% to 1.5%. Stroke was the most common target organ involvement in Asians who presented with hypertensive emergencies. Although most hypertensive emergency patients required hospitalization, the mortality rate was low. Given the current lack of data among Asian countries, a multinational data repository and Asian guidelines on hypertensive emergency management are mandatory.